The professional protection officer : practical security strategies and emerging trends - Davies, Sandi J.; Lawrence, Fennelly (Waltham : Elsevier, 2020)
"Provides a three-pronged approach to precision medicine that is focused on investigators, practitioners and healthcare providers Covers disease groups and ancillary information about techniques, resources and consequences Follows a structured blueprint, ensuring essential chapters items are not overlooked"--